Установка электрохимического профилирования для диагностирования эпитаксиальных структур GaAs - Vakiv, N. M.; Zaverbniy, I. R.; Zayachuk, D. M.; Krukovsky, S. I.; Mrykhin, I. O. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
An electrochemical profiling setup for semiconductor structures has been developed, in which the concentration of free charge carriers is determined from the capacitance–voltage characteristics of the electrolyte–semiconductor barrier, while scanning through the thickness of epitaxial layers is performed by photoelectrochemical etching of the semiconductor. Using GaAs epitaxial structures as an example, high measurement accuracy of carrier concentration to a depth of at least 10 μm has been demonstrated.